THE IMPACT OF GOVERNMENT SUPPORT ON THE DEVELOPMENT OF FOOTBALL INFRASTRUCTURE IN UZBEKISTAN (Proximus Journal of Sports Science and Physical Education, 2025)
The development of football infrastructure in Uzbekistan has gained significant momentum in recent decades, largely due to the growing involvement and support of the national government. This article explores the extent to which government policies and initiatives have contributed to the advancement of football facilities across the country. By examining investments in stadiums, training centers, and youth academies, the paper assesses the outcomes of state-driven strategies on both grassroots and professional levels of football. The study is based on qualitative and quantitative data, including government reports, expert opinions, and media coverage. The findings suggest that while substantial progress has been achieved, there remain challenges related to regional disparities and sustainability. The article concludes with recommendations for optimizing government support to ensure balanced and long-term development of football infrastructure throughout Uzbekistan.